Recombinant antibody production evolves into multiple options aimed at yielding reagents suitable for application-specific needs - de Marco, Ario (Microb Cell Fact, 2015)
BACKGROUND: Antibodies have been a pillar of basic research, while their relevance in clinical diagnostics and therapy is constantly growing. Consequently, the production of both conventional and fragment antibodies constantly faces more demanding challenges for the improvement of their quantity and quality. The answer to such an increasing need has been the development of a wide array of formats and alternative production platforms. This review offers a critical comparison and evaluation of the different options to help the researchers interested in expressing recombinant antibodies in their choice. RESULTS: Rather than the compilation of an exhaustive list of the recent publications in the field, this review intendeds to analyze the development of the most innovative or fast-growing strategies. These have been illustrated with some significant examples and, when possible, compared with the existing alternatives. Space has also been given to those solutions that might represent interesting opportunities or that investigate critical aspects of the production optimization but for which the available data as yet do not allow for a definitive judgment. CONCLUSIONS: The take-home message is that there is a clear process of progressive diversification concerning the antibody expression platforms and an effort to yield directly application-adapted immune-reagents rather than generic naked antibodies that need further in vitro modification steps before becoming usable.